Kayseri Hancerli Sultan Vakfi Bedesteni in the Context of the Ottoman Bedestens - Oncel, Fernaz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2014)
The deeply-rooted commercial structure tradition of Kayseri is based on the city's constant and centuries-old role in international trade and commerce. Throughout the Seljuk period, Kayseri's bazaars were located outside the city walls, in the immediate vicinity of the city. Building of commercial structures in the citadel itself and the centre of the city began during Ottoman times, the period in which the city's traditional commercial structure began to appear and grow. In 1497, the Sanjak Bey of Kayseri, Mustafa bin Abdulhay, constructed the Kayseri Hancerli Sultan Vakfi Bedesteni, surrounded by 38 stores, and thus began the establishment of the commercial fabric of the city. Over time, the Bedesten has changed both physically and functionally. These changes have been for the worse and have led to the Bedesten and its surroundings being defined as an area of declining trade. Factors that have negatively affected the structure's physical make-up include environment, natural disasters, improper restoration, deliberate corruption, and haphazard changes made by users. Economic factors playing a role in its decline include changes to its original function as a 'shopping' centre, its traditional customer base, and the type and quality of goods traded there. The Bedesten is discussed here under four headings; Introduction, Bedestens as Ottoman Commercial Structures, Kayseri Hancerli Sultan Wakf Bedesten, Evaluation, and Conclusions.
Keywords: Architecture